SISTEM PENJUALAN AIR ISI ULANG MENGGUNAKAN ARDUINO BERBASIS INTERNET OF THINGS (IOT) - Muhammad Burhan; Joko Priambodo (CV. Multi Kreasi Media, 2023)
Plastic waste is one of the main causes of climate change. Because, from the production process to the disposal and management stage, plastic waste emits a lot of greenhouse gases into the atmosphere. Plastic is made from petroleum by the process of converting petroleum components into small molecules called monomers. The activity of producing plastics requires about 12 million barrels of oil raw materials. The difficulty of people getting tools / places to fill drinking water bottles in public spaces indirectly increases the purchase of drinking water that uses single-use plastic bottles. To solve this problem, a tool was created that is able to refill drinking water bottles without having to add single-use plastic drinking water bottle waste. In this study, it uses the prototype implementation method where the flow and stages used include needs analysis, building prototypes, prototype evaluation, tool implementation, and testing. The results of this study are in the form of tools and applications for the Internet of Things-based refill water sales system.